Microstructure, Microhardness, Fracture Toughness, and Abrasive Wear of In-Situ Synthesized TiC/Ti-Al Composite Coatings by Cold Spraying Combined with Heat Treatment - Xiao Chen (Coatings, 2021)
TiAl intermetallic compounds, as a new kind of high-performance light-weight structural material, are widely applied in many fields. Titanium carbide (TiC) as the reinforcing phase could improve the mechanical properties, wear resistance, and heat-resistance stability of TiAl intermetallic compounds. Ti(Al, C) mixture powders were deposited by cold spraying at gas temperature of 250 °C, 450 °C, and 550 °C. Then, Ti(Al, C) coatings were annealed at temperatures of 650 °C for different times and following holding at 1100 °C for 3 h. The microstructure, microhardness, fracture toughness, and abrasive wear of Ti-Al composite coatings were investigated. The research results were that the particle size of mixture powders decreased as the ball milling time prolonging. Ti(Al) solid solution appeared in the mixture powders as the milling time increased to 30 h. The average porosity of the coating sprayed at 550 °C was the lowest (0.85%). The as-sprayed coatings exhibited the same phase compositions with the mixture powders. The coating sprayed at gas temperature of 550 °C has the highest microhardness and the lowest weight loss. Ti-Al intermetallic was in-situ synthesized after annealing at 650 °C. The average porosity of the annealed coating (sprayed at 450 °C) was the lowest. The content of Ti-Al intermetallic compounds of the annealed coating sprayed at 450 °C is the highest. The X-ray diffraction (XRD) analysis results are consistent with the EDS analysis of the annealed coatings after annealing at 650 °C. Ti-Al intermetallic compounds were almost completely formed in the three kinds of the coatings after annealing at 650 °C for 20 h and following holding at 1100 °C for 3 h. TiAl and TiAl3 intermetallic phases were in-situ synthesized in the coatings based on the energy dispersive spectroscopy (EDS) and XRD analysis. TiC was also in situ synthesized in the coatings as the annealing temperature increased to 1100 °C. The annealed coating (sprayed at 450 °C) has the highest microhardness, fracture toughness, and wear resistance properties after annealing at 1100 °C for 3 h.